2010
DOI: 10.1037/h0100680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the relative effectiveness of different kinds of reinforcers: A PEM approach.

Abstract: The purpose of the present study was to apply the percentage of data points exceeding the median of baseline phase (PEM) approach for a meta-analysis of single-case experiments to compare the relative effectiveness of different kinds of reinforcers used in behavior modification. Altogether 153 studies were located, which produced 1091 effect sizes. The grand mean of the 153 PEM scores was .92. The main finding was that among the positive reinforcers, "activities" was the most effective (PEM score = .95) while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 138 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Positive reinforcement is giving a reinforcer to strengthen the targeted behavior (Miltenberger, 2016;Martin & Pear, 2015). Some research has found that positive reinforcement provides internal motivation and clear expectations for children's behavior (Ma, 2010;Wilder, 2005). Applying positive reinforcement helps children comprehend adult expectations and behave appropriately in an environment.…”
Section: Introductionmentioning
confidence: 99%
“…Positive reinforcement is giving a reinforcer to strengthen the targeted behavior (Miltenberger, 2016;Martin & Pear, 2015). Some research has found that positive reinforcement provides internal motivation and clear expectations for children's behavior (Ma, 2010;Wilder, 2005). Applying positive reinforcement helps children comprehend adult expectations and behave appropriately in an environment.…”
Section: Introductionmentioning
confidence: 99%